Peduli Lingkungan Melalui Program Penanaman Pohon di Negeri Kilang Kota Ambon - Ronald D. Hukubun; Marlin C. Wattimena; Laury Marcia Chara Huwae; Michele F. C. Usmany; Gloria M Souissa; Gian Rumahlatu (Fakultas Teknik Universitas Cenderawasih, 2023)
Environmental care activities carried out in the form of reforestation in Negeri Kilang are also an implementation of the Pattimura University KKN student program, the first batch of Class L, aimed at increasing the knowledge of the Negeri Kilang community about the role and function of plants, as well as creating the character of the Negeri Kilang community who care about the environment. Carrying out activities is a form of assistance in the field as well as outreach to village communities regarding reforestation efforts as a form of protecting and preserving the environment. The results of this tree planting activity are the planting of clove, mahogany, ironwood and durian tree seedlings in reforestation locations and in hamlets/community gardens which can be utilized according to their intended purpose to make land use more efficient, apart from optimizing ecological functions, as well as providing economic value for the people of the Negeri Kilang.